Preperitoneal Fat Grafting Inhibits the Formation of Intra-abdominal Adhesions in Mice - Mervi Laukka; Erika Hoppela; Jemiina Salo; Pia Rantakari; Tove J. Gronroos; Katri Orte; Kaisa Auvinen; Marko Salmi; Heidi Gerke; Kerstin Thol; Emilia Peuhu; Saila Kauhanen; et al. (Journal of Gastrointestinal Surgery, 2022)
BACKGROUND:
Adhesion formation contributes to postoperative complications in abdominal and gynaecological surgery. Thus far, the prevention and treatment strategies have focused on mechanical barriers in solid and liquid form, but these methods are not in routine use. As autologous fat grafting has become popular in treatment of hypertrophic scars because of its immunomodulatory effects, we postulated that fat grafting could also prevent peritoneal adhesion through similar mechanisms.
METHODS:
This was a control versus intervention study to evaluate the effect of fat grafting in the prevention on peritoneal adhesion formation. An experimental mouse model for moderate and extensive peritoneal adhesions was used (n = 4-6 mice/group). Adhesions were induced mechanically, and a free epididymal fat graft from wild type or CAG-DsRed mice was injected preperitoneally immediately after adhesion induction. PET/CT imaging and scaling of the adhesions were performed, and samples were taken for further analysis at 7 and 30 days postoperation. Macrophage phenotyping was further performed from peritoneal lavage samples, and the expression of inflammatory cytokines and mesothelial layer recovery were analysed from peritoneal tissue samples.
RESULTS:
Fat grafting significantly inhibited the formation of adhesions. PET/CT results did not show prolonged inflammation in any of the groups. While the expression of anti-inflammatory and anti-fibrotic IL-10 was significantly increased in the peritoneum of the fat graft-treated group at 7 days, tissue-resident and repairing M2 macrophages could no longer be detected in the fat graft at this time point. The percentage of the continuous, healed peritoneum as shown by Keratin 8 staining was greater in the fat graft-treated group after 7 days.
CONCLUSIONS:
Fat grafting can inhibit the formation of peritoneal adhesions in mice. Our results suggest that fat grafting promotes the peritoneal healing process in a paracrine manner thereby enabling rapid regeneration of the peritoneal mesothelial cell layer.